Study of Infertility in Females by Laparoscopy in Remote Area - Zubair Un Nisa Butt; Ghulam Hasnain Khan (Journal of Rawalpindi Medical College, 2009)
Background: To evaluate the role of laparoscopy in diagnosis and management of problems related to infertility. Methods: The descriptive study was conducted on 40 patients of infertility over a period of one year and nine months from April 2007 to December 2008. After complete history and examination, basic endocrinological investigations and semen analysis were done in infertile couple. Laparoscopy was done after pre - operative fitness under general anaesthesia. Results: The average age of women was 30 years . About one third of patients were brought within 5years , another third in 10 years and remaining third more than 10 years after marriage . 82.5% case were of primary infertility ,5% secondary infertility ,and 12.5% presented with primary amenorrhoea and infertility .Tubal block was one of the major causes of infertility . Adhesionolysis was done in 7.5%cases.ATTwas given on clinical grounds in 2.5% cases. Six patients conceived after treatment with healthy outcome. Conclusion: Infertile couple should be thoroughly investigated . Laparoscopy in infertility can be used for a definite diagnosis and treatment with good outcome.